Pengaruh Pengetahuan Dan Kesadaran Pajak Terhadap Kemauan Untuk Membayar Pajak - DJO, CHETVIN REINHARD CLIFORD; Ismail, Marthinus; Susanti, Mila (Fakultas Ekonomi Universitas Advent Indonesia, 2024)
The willingness to pay taxes should be instilled in the community as early as possible. Therefore, one of the strategies carried out by the government is the Tax Goes to School program. This program is used to increase the knowledge and awareness of prospective taxpayers in order to awaken the willingness to pay taxes. In line with the government program, this research focuses on the perception of students in West Bandung on taxation as a population. Students who have gained knowledge about taxes as prospective taxpayers. It was found that 60 respondents filled out a questionnaire that could be used as a sample with several sample criteria. The data was analyzed using descriptive and regression analysis which began with validity and reliability tests and classical assumption tests. The results of the research data processing illustrate that tax knowledge and awareness significantly affect the willingness to pay taxes based on student perception both partially and simultaneously.